2019
DOI: 10.3389/fgene.2019.00700
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Single Nucleotide Polymorphisms Related to the Resistance Against Acute Hepatopancreatic Necrosis Disease in the Pacific White Shrimp Litopenaeus vannamei by Target Sequencing Approach

Abstract: Acute hepatopancreatic necrosis disease (AHPND) is a major bacterial disease in Pacific white shrimp Litopenaeus vannamei farming, which is caused by Vibrio parahaemolyticus . AHPND has led to a significant reduction of shrimp output since its outbreak. Selective breeding of disease-resistant broodstock is regarded as a key strategy in solving the disease problem. Understanding the relationship between genetic variance and AHPND resistance is the basis for marker-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…In 2018, 95 full-sib families with an average body weight of 2.10 g were selected for evaluation of resistance. For the challenge experiment, VP AHPND was prepared according to the method described by Zhang Q. et al (2019). About 100 healthy shrimp from each family were subjected to VP AHPND immersion infection.…”
Section: Selection Resistant and Susceptible Families Against Acute Hepatopancreatic Necrosis Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, 95 full-sib families with an average body weight of 2.10 g were selected for evaluation of resistance. For the challenge experiment, VP AHPND was prepared according to the method described by Zhang Q. et al (2019). About 100 healthy shrimp from each family were subjected to VP AHPND immersion infection.…”
Section: Selection Resistant and Susceptible Families Against Acute Hepatopancreatic Necrosis Diseasementioning
confidence: 99%
“…So far, several genes associated with disease resistance have been reported in aquatic animals. Polymorphism of LvALF and TRAF6 was reported to be associated with the resistance to WSSV in shrimp (Wang et al, 2011;Liu et al, 2014b;Liu et al, 2014a;Yu et al, 2017;Zhang Q. et al, 2019). A major quantitative trait locus (QTL) for the resistance of Atlantic salmon (Salmo salar) against infectious pancreatic necrosis (IPN) was discovered, which has been already applied in marker-assisted breeding of IPN-resistant fish (Houston et al, 2008;Moen et al, 2009;Woldemariam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In shrimp, the role of SNPs was demonstrated for use in construction of linkage maps (Baranski et al, 2014;Yu et al, 2015;Jones et al, 2017) trait-specific association studies (Robinson et al, 2014;Santos et al, 2018;Zhang Q. et al, 2019;Janpoom et al, 2020), genetic characterization (Perez-Enriquez et al, 2018;Vu et al, 2020) and parentage testing (Henshall et al, 2014;Sellars et al, 2014). In this study, we report 2,572 nonsynonymous SNPs, of which 46 might have potential to impact the functions of coding proteins.…”
Section: Discussionmentioning
confidence: 85%
“…However, the modification of genes needs full understanding of their functions and the functional networks that can be affected before the edition strategy can be tested. As example of the appli- Molecular markers based on single nucleotide polymorphisms (SNPs) have been recently implemented for selecting for growth performance, 113,114 resistance to V. parahaemolyticus in P. vannamei, 111,115 parvovirus in P. mergulensis 116 or even different stressors such as nitrite concentration. 117 Recently, Pooljun et al 118 have found an association between a SNP in the anti-lipopolysaccharide factor 3 (ALF3) and resistance to WSSV in P. monodon.…”
Section: Future Per S Pec Tive S and Con Clus Ionsmentioning
confidence: 99%